Regulation of advanced glycation end product (AGE) receptors and apoptosis by AGEs in osteoblast-like cells - Mercer, Natalia (2007)
Advanced glycation end products (AGEs) have been proposed as the pathological mechanisms underlying diabetic chronic complications. They may also play a role in the pathogenesis of diabetic osteopenia, although their mechanisms of action remain unclear. We investigated the protein (immunofluorescence) and gene expression (realtime RT-PCR) of two receptors for AGEs, RAGE and galectin-3, as well as their regulation by AGEs, and the apoptotic effect on osteoblast-like cells (UMR106 and MC3T3E1) in culture. AGEs up-regulated the expression of RAGE and galectin-3 in both cells lines. These effects were accompanied by an increase in the corresponding mRNA in the non-tumoral MC3T3E1 but not in the osteosarcoma UMR106 cells. Finally, we demonstrated that a 24 h exposure to AGEs induced apoptosis in both cell lines. Thus, AGEs-receptors may play important roles in the bone alterations described in aging and diabetic patients.